Rehabilitation arrangements for narcotics adults based on justice in significance - Mamangkey, Jesicha Yenny Susanty; Prasetyo, Teguh; Yudianto, Otto (Technium Social Sciences Journal, 2022)
The Narcotics Law has guaranteed arrangements for medical and social rehabilitation efforts for Narcotics Abusers and Addicts where judges do not sentence prison sentences but sentence them to undergo rehabilitation. The application of such a law will of course make this country not like it is now where prisons are over capacity, prisons become a center for the distribution of narcotics and other criminal offenses due to abusers being imprisoned. Arrangements regarding medical and social rehabilitation cannot be separated from the philosophical basis existence of state as stated in 1945 Constitution Republic of Indonesia. The constitution, which contains the Pancasila philosophy, clearly emphasizes that state must provide protection for all Indonesians, including providing health protection. Thus, the nature rehabilitation arrangements as one of goals in Narcotics Law is protection of citizens and nation building.